Paroxysmal nocturnal haemoglobinuria, diagnosis and haematological findings, first report from Iran, model for developing countries. Issue 2 (8th March 2022) - Jahangirpour, Mohammadali; Vahedi, Amirali; Baghdadi, Hamed; Madani, Tahereh; Behvarmanesh, Ali; Alidadi, Mohammad; Boroojerdi, Mohadese Hashem; Mohammaei, Saba; Poopak, Peyvand; Poopak, Amirhossein; Pour, Gelareh Khosravi; Poopak, Behzad
Abstract: Since paroxysmal nocturnal haemoglobinuria (PNH) was first described in 1881, the diagnosis and follow‐up patients diagnosed with the illness has remained an area of concern, with several different techniques of varying sensitivity having been described in the literature for both the diagnosis and monitoring treatment of the disease. PNH is a rare and life‐threatening disease that manifests symptoms of haemolytic anaemia. Hence, a quick and reliable technique for precise diagnosis would be crucial. PNH patients who have previously been diagnosed with aplastic anaemia or myelodysplastic syndrome carry small PNH clones and for more than a century traditional method with low sensitivity was used for such patients. In 2010, the International Clinical Cytometry Society described a highly sensitive method for detection and quantification of different types of PNH clones using multi‐colour flow cytometry. In this method, a three‐colour flow cytometer is essential to detect PNH affected cells amongst monocytes and granulocytes. This started a new era in the diagnosis of patients who carry small clones of PNH cells. Before this, flow cytometric analysis was used only for detection of PNH cells amongst erythrocytes. By using flow cytometry instruments with more light sources, the sensitivity of detection and quantification of PNH clones would be augmented. However, standardisation and crosstalk compensation would be the most concerning issue. For the first time in Iran, we set up and standardised multi‐colour flow cytometry technique to detect PNH cells in erythrocytes and leukocytes at Payvand medical laboratory.